Approach to cytological indeterminate thyroid nodules - Bongiovanni, Massimo (Gland Surg, 2019)
The indeterminate thyroid nodules diagnosed by fine-needle aspiration cytology (FNAC)represents a problem for both cytopathologists and clinicians. The former sometimes use this diagnostic category as a sort of basket, putting in cases that they do not know exactly how to classify. The latter are faced with a highly variable risk of malignancy and consequently the management remains a challenge. On the histopathological side, the new WHO classification of tumors of the thyroid introduced the concept of tumors with uncertain and low malignant potential, and the concept of non-invasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP), whose prognosis and management are still to be completely elucidated. While the risk of malignancy of the indeterminate diagnostic category has decreased due to the re-classification of certain types of papillary thyroid carcinomas of the follicular variant into a low malignant potential form (the NIFTP), cases diagnosed cytologically as indeterminate will probably increase in the future to avoid false positive diagnosis. Thus, the indeterminate thyroid diagnostic category still remains a challenge, both at the diagnostic level and for its management. The new version of the Bethesda system for reporting thyroid cytopathology suggests managing these patients with a repeat FNA, diagnostic lobectomy and/or molecular testing.